Coping strategies on food insecurity among disaster-affected households in selected Philippine provinces. - Talavera, M. T. M. (Compendium of Human Ecology Researches in the Philippines, 2003)
Households living in the five provinces of Region IV-A and V have been consistently affected by damages brought about by natural disasters. In addition to physical damages and loss of lives, survivors are faced with transitory and chronic food insecurities. Thus, disaster-affected households have developed coping strategies within the framework of food and nutrition security. Coping strategies reported were related to food availability, accessibility, utilization and stability. In an effort to become food secure, households relied on food rations, assistance from relatives, neighbors, and friends. They also reduced food consumption and used savings or sold properties. Based on the findings, it is recommended that interventions such as nutrition education, food diversification, financial assistance, and food assistance be integrated in existing disaster management plans of local government units to mitigate the impact of disasters.